Deployment of metal-organic frameworks as robust materials for sustainable catalysis and remediation of pollutants in environmental settings. (June 2021) - Ali, Nisar; Bilal, Muhammad; Khan, Adnan; Ali, Farman; Yang, Yong; Malik, Sumeet; Din, Salah Ud; Iqbal, Hafiz M.N.
Abstract: From metal-organic chemistry, metal-organic frameworks (MOFs) are of supreme interest for catalysis and environmental settings. Owing to anthropogenic sources and booming industrial practices, the most challenging issue is increased water pollution and environmental insecurity. For instance, several types of synthetic dyes are toxic up to a certain extent, as emerging organic contaminants (EOCs) pose adverse environmental and potential health consequences. A gradual increase in the contamination sources and unpredictable environmental changes in terms of anthropogenic pollution severely affect both water availability and distribution. Therefore, the treatment of dyes containing wastewater matrices for water resource generation is one of the most important tasks, which must be addressed effectively. With structural tunability, MOFs have been appearing as a robust tool for remediating toxic pollutants from wastewater matrices. Moreover, the promising functionality, structural tunability, robust catalytic attributes, compatibility, large surface area, stability in water, and ease in surface functionalization make MOFs one of the considerable materials of interest. This review work spotlights the present-day progress related to MOFs and their catalytic and adsorptive chemistry for a sustainable environment. Following a brief introduction, the characteristic rendering MOFs, as adsorbents, are given with prominent examples. Next, several synthesis routes as a roadmap to engineer MOFs are discussed. From the applied perspective, the adsorptive and catalytic potentialities of MOFs as given by addressing sustainable mitigation of toxic dyes. The last section of the work illustrates key challenging issues and future directions by considering the suiting importance of MOFs. Graphical abstract: Image 1 Highlights: Metal-organic frameworks (MOFs) exhibit fascinating structural and functional attributes. Working chemistry of MOFs aid in mitigating toxic pollutants from wastewater. The characteristic rendering MOFs interesting matrices for environmental settings are presented.